Islamic Family Law and the Right to Divorce: A Critical Analysis of Women’s Legal Empowerment in Pekanbaru - Desra, Rio; Putra, Andri; Rinaldi, Aldi; Rahma, Maulidya Nur; Netti, Mesra (Yayasan Marwah Madani Riau, 2025)
This study aims to critically examine the extent to which Islamic family law in Pekanbaru conducted from January to March 2025 empowers women in exercising their right to divorce. Grounded in a socio-legal and gender justice framework, the research explores both formal legal provisions and the lived experiences of Muslim women navigating divorce processes through the Religious Courts. Using a qualitative method, data were collected through in-depth interviews with divorced women, judges, and legal practitioners, and content analysis of relevant legal documents and court decisions. The findings reveal a complex interplay between religious norms, legal structures, and cultural expectations. While Islamic family law formally recognizes women's rights to divorce through mechanisms such as khulʿ and fasakh, bureaucratic hurdles, patriarchal interpretations, and social stigma often limit women's access to these rights in practice. Women who successfully obtained a divorce demonstrated strong legal awareness and support networks, suggesting that empowerment is highly dependent on socio-economic and educational factors. The study discusses the gap between normative Islamic principles that uphold justice and the structural barriers that hinder their realization in practice. It concludes that enhancing women's legal empowerment requires reforming procedural aspects of family law and promoting community-level awareness and gender-sensitive interpretations of Islamic jurisprudence.